Proposition Analysis of Fixed Broadband Services Based on Product Segmentation And Purchasing Power of Urban Society - Santoso, Triyono Budi (ComTech: Computer, Mathematics and Engineering Applications, 2016)
Tight competition in the broadband industry has forced the provider to have a good product propotition and strategy in the market, including market segmentation and type of services delivered based on customer’s expextation and intention to buy. This research aims to make a product proposition based on two major criteries in fixed broadband service, which are speed and price of the product, by looking into the competition in existing market (competitor’s product). As many players in Indonesia have created very tight situation, the will be launched product should have an attractive matter or differentiation in order to compete and get a “buy in” of the customer. In the research, some analysis was conducted across all the propositions by spreading questionnaires to respondents in urban area especially in Jakarta and Bandung, thus the provider can create product with an appropriate specifications to answer the needs of customers on their affordable price to buy. Some close-ended questions in the questionairres were scaled and performed by basic statistical approach methods. The result shows that product with affordable price is still become the choice of respondents in each segment (low, medium and high income). Price list per speed which is fitted to any segments is also suggested in this research. The result of the research can also be used to develop the product as a differentiation to be the choices and preferencesof customers.